Regulation of bone metabolism by Wnt signals - Kobayashi, Yasuhiro (J Biochem, 2016)
Wnt ligands play a central role in the development and homeostasis of various organs through β-catenin-dependent and -independent signalling. The crucial roles of Wnt/β-catenin signals in bone mass have been established by a large number of studies since the discovery of a causal link between mutations in the low-density lipoprotein receptor-related protein 5 (Lrp5) gene and alternations in human bone mass. The activation of Wnt/β-catenin signalling induces the expression of osterix, a transcription factor, which promotes osteoblast differentiation. Furthermore, this signalling induces the expression of osteoprotegerin, an osteoclast inhibitory factor in osteoblast-lineage cells to prevent bone resorption. Recent studies have also shown that Wnt5a, a typical non-canonical Wnt ligand, enhanced osteoclast formation. In contrast, Wnt16 inhibited osteoclast formation through β-catenin-independent signalling. In this review, we discussed the current understanding of the Wnt signalling molecules involved in bone formation and resorption.